Participation of a foreign investor for supplying a clean water of Deli Serdang regency of North Sumatera province (case study: Pt. Tirta Sumut, a joint venture company) - Sjahril Effendy (Proceedings of AICS - Social Sciences, 2017)
The regional government of Deli Serdang enhances a chance to foreign investors to invest in clean water sector. It is adjusted to the Laws No. 25 of 2007 regarding Investment, providing a chance, protection (assurance) and legality for any foreign investors of joint venture company in clean water sector of Deli Serdang Regency. One of the interesting foreign investors is Water Fund Holland BV partnered with PDAM Tirtanadi of North Sumatra Province by establishing a joint venture named PT. Tirta Sumut producing a clean water at Sei Ular Water Treatment Plant in capacity of 120 liters/second. The present study intends to find know the implementation of corporation partnership and how PT. Tirta Sumut commit to complete the main task of managing, operating and maintaining all the existing production systems at Sei Ular Water Treatment Plant (WTP) for 15 (fifteen) years. The method used in the study was a descriptive analysis intended to describe the problems and facts related to the implementation of such a joint venture.  The collected data included primary and secondary ones. The data collection method used a field study by interview for collecting the primary data and library study for collecting the secondary data.  The collected data were then analyzed descriptively. Based on the result of the study, it can be concluded that the implementation of such a company partnership between WFH BV and PDAM Tirtanadi for establishment of such a joint venture was successfully carried out and the produced clean water has been distributed to the regional customers of Lubuk Pakam by PDAM Tirtanadi Branch of Deli Serdang.